2022
DOI: 10.1002/adsc.202101380
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Binaphthyl‐Based Iodonium Salt (Hypervalent Iodine(III)) as Hydrogen‐ and Halogen‐Bonding Bifunctional Catalyst: Insight into Abnormal Counteranion Effect and Asymmetric Synthesis of N,S‐Acetals

Abstract: Asymmetric construction of chiral N,S‐acetal skeletons is important because they are widely present in natural products and pharmaceuticals. Halogen‐bonding is a unique interaction that has been an organic synthesis focus, although research into chiral variants is limited. Halonium salts have been found to act as halogen‐bonding catalysts and asymmetric catalysis using chiral bromonium salts under basic conditions was recently discovered by our group. Herein, we report the asymmetric syntheses of chiral N,S‐ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 82 publications
0
34
0
2
Order By: Relevance
“…The bromonium catalyst 42a was used in the vinylogous Mannich reaction of cyanomethyl coumarins 43 with ketimines 44 , delivering the coupling products 45 in high yields and ee up to 96% [ 100 ]. The iodonium catalyst 42b was, however, more powerful in the asymmetric addition of bulky thiols to ketimines 44 for the formation of N,S-acetal products 46 in high yields and enantioselectivities [ 101 ]. In both cases, the DFT-calculated plausible key intermediate structures showed that both XBs and HBs concur with the observed high enantioselectivity induction ( Figure 21 ).…”
Section: Asymmetric Catalysismentioning
confidence: 99%
“…The bromonium catalyst 42a was used in the vinylogous Mannich reaction of cyanomethyl coumarins 43 with ketimines 44 , delivering the coupling products 45 in high yields and ee up to 96% [ 100 ]. The iodonium catalyst 42b was, however, more powerful in the asymmetric addition of bulky thiols to ketimines 44 for the formation of N,S-acetal products 46 in high yields and enantioselectivities [ 101 ]. In both cases, the DFT-calculated plausible key intermediate structures showed that both XBs and HBs concur with the observed high enantioselectivity induction ( Figure 21 ).…”
Section: Asymmetric Catalysismentioning
confidence: 99%
“…[23] Furthermore, recently the related bromolium and chlorolium analogs have been introduced in catalysis. [13], [14] As bromolium catalysts sometimes outperformed iodolium ones, X the order in Lewis acidity remained unclearuntil very recently, when Stuart and co-workers reported insights on the nature of bonding and behavior of these diarylhalonium ions. [24] Herein, we aim to finally elucidate the origin of the higher Lewis acidity of iodolium vs. diaryliodonium salts via an in-depth analysis of the hybridization of these species and via energy decomposition analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Halogen bonding (XB) [10] denotes the attraction of electrophilic halogen substituents to Lewis bases, and typically iodine(I) systems have been used in most cases. Lately, iodine(III) derivatives, and in a lesser extent bromine [11][12][13][14] and chlorine [14] equivalents, have received increasing attention as potent Lewis acids. A first application in organocatalysis was reported based on diaryliodonium ions like the prototypical compound 1 (Figure 1), even though the exact mode of activation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While in one case the latter produced markedly higher yield and somewhat improved enantioselectivity, [13] the iodolium catalyst clearly outperformed bromolium (and chlorolium) alternatives in a second study. [14] Due to these conflicting findings and the complex nature of the catalysts employed, it is thus unclear whether iodolium or bromolium/chlorolium are in principle stronger Lewis acidseven though the higher polarizability and lower electronegativity of iodine makes iodolium the most likely candidate. Bifunctional chiral catalysts including a iodolium, bromolium or chlorolium group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation